Majewski syndrome (short‐rib polydactyly syndrome type II): Prenatal diagnosis and histological features of chondral growth plate, liver and kidneys - Tonni, Gabriele; Palmisano, Marcella; Ventura, Alessandro; Grisolia, Gianpaolo; Baffico, Ave Maria; Pattacini, Pierpaolo; Bonasoni, Maria Paola; De Felice, Claudio (Congenital anomalies, 2014)
The Majewski syndrome or short rib‐polydactyly syndrome (SRPS) type II is a lethal skeletal dysplasia characterized by severe IUGR (intrauterine growth restriction) and dysmorphic face, polydactyly, relatively proportionate head size at birth with later progression to microcephaly. A case of second trimester ultrasound diagnosis of SRPS type II is reported with review of the medical record of previous observed cases. Postmortem examination and radiogram confirmed the clinical diagnosis. Histological examination of the femoral epypheseal chondral plate showed an expanded and irregular hypertrophic zone. Moreover, characteristic cortico‐medullary cysts of both kidneys and portal fibrosis were also demonstrated; findings consistent with the broad phenotypic spectrum of this rare skeletal disease.